2013
DOI: 10.2105/ajph.2012.301115
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in Disability Among Adults: A Multicountry Study Using the World Health Survey

Abstract: Integrating equity components into the monitoring of disability trends would help ensure that interventions reach and benefit populations with greatest need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 21 publications
9
108
1
3
Order By: Relevance
“…4.6 and Appendix A3). 12 This result is consistent with results from Hosseinpoor et al (2013) using an asset quintile, a disability measure similar to that in WHOWorld Bank (2011) and 2002 World Health Survey data for 49 countries, including Ethiopia and Malawi. Table 4.7 gives descriptive statistics of households across functional status.…”
Section: Severe Difficultysupporting
confidence: 73%
“…4.6 and Appendix A3). 12 This result is consistent with results from Hosseinpoor et al (2013) using an asset quintile, a disability measure similar to that in WHOWorld Bank (2011) and 2002 World Health Survey data for 49 countries, including Ethiopia and Malawi. Table 4.7 gives descriptive statistics of households across functional status.…”
Section: Severe Difficultysupporting
confidence: 73%
“…Relevant aspects in the process of health social determinants seem to be interconnected with DIS. Correlations between DIS and SES indicators, such as income 3,12,25 , educational level 3,12 , and occupation 1,5 , are observed in scientific findings. In this study, income for both sexes and educational level for men were inversely associated with DIS.…”
Section: Discussionmentioning
confidence: 91%
“…A recent multi-country study showed that disability was consistently more prevalent in the poorest than richest quintiles. 46 In their population-based study, Cobigo and colleagues 47 showed that the proportion of Ontario women with intellectual and developmental disabilities who were not screened for cervical cancer was nearly twice that of women without these disabilities. Multimorbidity has been strongly associated with preventable hospital admissions, and this risk is exacerbated by socioeconomic deprivation.…”
Section: Cmaj Openmentioning
confidence: 99%